Individual Responsibility for Health: Decision, not Discovery - Yoder, Scot D. (The Hastings Center report, 2002)
Health policy sometimes hinges on claims about the responsibility borne by people or corporations for health outcomes. We don't want these claims to be arbitrary, so we construe them as discoveries of plain fact. But we're mistaken. They are interwoven with our values and social institutions. Recognizing that they are allows us to debate them more honestly and thoroughly.